JENIS RAYAP YANG MENYERANG RUMAH PENDUDUK DI KECAMATAN SIDOAN KABUPATEN PARIGI MOUTONG SULAWESI TENGAH - Nego, Elisyafan Abet; Hapid, Abdul; Muthmainnah, Muthmainnah; Erniwati, Erniwati (Universitas Tadulako, 2020)
Termites are one type of destroyer that has a very large role in causing damage to buildings. The ability of termites in damaging there is a very large complexity, broad cruising and adaptability to the environment is quite good. This study aims to determine the types of termites that attack people's homes and the usefulness of this study in order to provide information to the public about the types of termites and the danger of termite attacks on housing in Sidoan District, Parigi Moutong Regency, Central Sulawesi. This research was conducted in August to October 2018, which was located in Sidoan District, Parigi Moutong Regency, Central Sulawesi. This study uses a multistage sampling method in sampling in each selected village. The choice of sampling is intentional for termite attacks and choice for coverage. The number of houses sampled were 30 houses consisting of 6 villages, with each village having 5 houses to collect. Then this data is analyzed descriptively. The results showed that there were two types of termites found in homes in the District of Sidoan, namely Nasutitermes sp and Coptotermes sp. Nasutitermes sp has the highest frequency (0.633%) followed by Coptotermes sp (0.367%).Keywords: Termite Types, Highest Frequency of Termite Presence